A novel fecal stable isotope approach to determine the timing of age‐related feeding transitions in wild infant chimpanzees. Issue 2 (21st October 2016) - Bădescu, Iulia; Katzenberg, M. Anne; Watts, David P.; Sellen, Daniel W.
Abstract: Objectives: Determining nutritional development in wild primates is difficult through observations because confirming dietary intake is challenging. Physiological measures are needed to determine the relative contributions of maternal milk and other foods at different ages, and time of weaning. We used fecal stable carbon and nitrogen isotopes (δ 13 C, δ 15 N) and fecal nitrogen concentrations (%N) from wild chimpanzees at Ngogo, Uganda, to derive physiological dietary indicators during the transition from total reliance on maternal milk to adult foods after weaning. Materials and Methods: We analyzed 560 fecal samples collected non‐invasively from 48 infants, their mothers, and 6 juvenile siblings. Most infant and juvenile samples (90%) were matched to samples collected from mothers on the same day. Isotopic assessments were compared with observations of nursing and feeding. Results: Infants ≤1 year old showed average δ 15 N, δ 13 C and %N ratios that were 2.0‰, 0.8‰ and 1.3% greater than their mothers, respectively, interpreted as trophic level effects. Although data collected on newborns were few, results suggest that solid foods were consumed within 2–5 months after birth. Trophic level differences decreased steadily after 1 year, which indicates a decreasing relative contribution of milk to the diet. Isotopic results indicated infants were weaned by 4.5 years old—more than a year earlier than observations of nipple contacts ceased, which revealed the occurrence of "comfort nursing." Juvenile isotopic signatures indicate no nursing overlap between siblings. Discussion: Our results resemble the stable isotope differences of human babies. This study contributes to a model of chimpanzee nutritional development required to understand early life history patterns in hominins.